Respiratory illness among Gulf War and Gulf War era veterans who use the Department of Veterans Affairs for healthcare. Issue 11 (26th August 2020) - Dursa, Erin K.; Tadesse, Bemnete E.; Carter, Caitlin E.; Culpepper, William J.; Schneiderman, Aaron I.; Rumm, Peter D.
Abstract: Background: Veterans of the 1990‐1991 Gulf War were exposed to a variety of toxic substances during their service that included several airborne hazards, but only a few small studies have assessed respiratory outcomes in Gulf War veterans. This paper presents population prevalence estimates and prevalence ratios of respiratory disease among Gulf War and Gulf War Era veterans who use VA healthcare. Methods: A total of 360, 909 Gulf War deployed veterans and 323, 638 Gulf War Era non‐deployed veterans were included in the analysis. Ten‐year period prevalence rates (PRs) for fifteen respiratory diseases were calculated for Gulf War and Gulf War Era veterans and period prevalence ratios comparing Gulf War veterans to Gulf War Era veterans were calculated. Results: The five respiratory conditions with the highest prevalence per 100, 000 veterans across both Gulf War deployed and Gulf War Era non‐deployed veterans (respectively) were: allergic rhinitis (8, 400 and 8, 041), chronic obstructive pulmonary disease (4, 763 and 4, 795), asthma (4, 685 and 4, 477), chronic airway obstruction (3, 983 and 4, 059), and chronic sinusitis (2, 863 and 2, 672). The adjusted PRs showed a small, but significantly increased, elevation in Gulf War‐deployed compared to Gulf War Era non‐deployed veterans for chronic bronchitis (PR 1.19; 95% CI 1.10, 1.28), emphysema (PR 1.11; 95% CI 1.01, 1.21), chronic airway obstruction (PR 1.09; 95% CI 1.07, 1.12), and chronic obstructive pulmonary disease (PR 1.09; 1.07, 1.11). Discussion: Gulf War veterans should continue to be monitored in the future to better evaluate the potential long‐term consequences on respiratory health.